Experimental approaches to hypothetical hormones: detection of a candidate ligand of the neu protooncogene. - Yarden, Y (1989)
There is a growing list of oncogenes encoding transmembrane tyrosine kinases that have structures reminiscent of growth factor receptors. In most cases, the ligands for these putative receptors are unknown. Using the neu oncogene as a model system, we have developed several experimental approaches for the detection of such hypothetical ligands. The following lines of evidence collectively imply that a candidate ligand of the neu-encoded oncoprotein is secreted by ras-transformed fibroblasts: Medium conditioned by ras transformants is able to induce down-modulation of the neu-encoded p185 and to activate its intrinsic tyrosine kinase activity in vitro. In addition, a rapid increase in the phosphorylation in vivo of tyrosine residues of the neu-encoded protein is induced by the conditioned medium. Finally, transfer of the neu gene into hematopoietic cells renders them mitogenically responsive to the conditioned medium. The possibility of indirect activation of the oncoprotein through other known receptors, especially the receptor for the epidermal growth factor, was experimentally excluded.